2016
DOI: 10.1080/00015458.2016.1165528
|View full text |Cite
|
Sign up to set email alerts
|

Post-Chernobyl incidence of papillary thyroid cancer among Belgian children less than 15 years of age in April 1986: a 30-year surgical experience

Abstract: Radiation exposure affected residents of countries (including Belgium) well beyond Ukraine and Belarus. This was demonstrated by a 1990 meteorological report. Over 30 years, there has been a persistent higher incidence of PTC among Belgian children below the age of 15 years at the time of the Chernobyl accident. This relationship with age has even been strengthened by the implementation of more sophisticated immunohistochemical biomarkers diagnostic technology since April 2011.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A Belgian (the distance between Brussels, the capital of Belgium, and Chernobyl is 2074km) study revealed that, over 30 years, there had been a persistent higher incidence of papillary thyroid cancer among children below the age of 15 years at the time of the Chernobyl accident. 14 Similarly, after the Fukushima accident, the average radiation dose-rates in the 59 municipalities of the Fukushima prefecture in June 2011 and the corresponding thyroid cancer detection rates in the period October 2011 to March 2016 showed statistically significant relationships. 15 However, the SHAMISEN Consortium recently did not recommend mass or population-based thyroid cancer screening, as the negative psychological and physical effects are likely to outweigh any possible benefit in affected populations.…”
Section: Discussionmentioning
confidence: 94%
“…A Belgian (the distance between Brussels, the capital of Belgium, and Chernobyl is 2074km) study revealed that, over 30 years, there had been a persistent higher incidence of papillary thyroid cancer among children below the age of 15 years at the time of the Chernobyl accident. 14 Similarly, after the Fukushima accident, the average radiation dose-rates in the 59 municipalities of the Fukushima prefecture in June 2011 and the corresponding thyroid cancer detection rates in the period October 2011 to March 2016 showed statistically significant relationships. 15 However, the SHAMISEN Consortium recently did not recommend mass or population-based thyroid cancer screening, as the negative psychological and physical effects are likely to outweigh any possible benefit in affected populations.…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Volosovets et al (2018) it was determined that excesses in the parameters of occurrence of diseases in the child population (+23.2%) occur particularly in radioactive contaminated territories compared to other areas. Increase in the risk of late cancer of the thyroid, especially among those who were irradiated by iodine in their childhood and teens, was pointed out by Michel et al (2016), Cherenko et al (2017) and Yamashita et al (2018). The latent period of radioactive-induced cancer of the thyroid, related to the explosion at the Chornobyl power plant, begun in 4-5th years after the explosion (Cherenko et al, 2017;Weiss, 2018) and lasts much longer than 30 years (Cherenko et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Doses of irradiation of the population of the contaminated territories are considered the most important characteristic of the consequences of the Chornobyl nuclear power plant explosion for people's health (Baverstock & Williams, 2006;Кravchenko, 2016;Michel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Radiation exposure seemed to be a risk factor for disease progression in the survival analysis using the Kaplan–Meier method. Some other studies have also revealed the dangers of radiation exposure in the development of thyroid cancer [ 25 , 26 ]. Most of these studies were based on the influences of nuclear pollution incidents; however, common radiation exposure incidents in daily life, such as radiotherapy and radioscopy, differ from nuclear pollution incidents in terms of dose, exposure time, and other factors.…”
Section: Discussionmentioning
confidence: 99%